E-learning 2.0 technologies and web applications in higher education - Pelet, Jean-Eric, 1976-, editor (Hershey, P.A. : Information Science Reference, an imprint of IGI Global, 2014)
"This book compiles the latest empirical research findings in the area of e-learning and knowledge management technologies assessment, highlighting specific comparisons and practices of e-m-learning and knowledge management technologies"--provided by publisher